2003
DOI: 10.1021/bi035447+
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the QacR Multidrug-Binding Protein with Structurally Diverse Ligands:  Implications for the Evolution of the Binding Pocket

Abstract: The QacR multidrug-binding repressor protein regulates the expression of the Staphylococcus aureus qacA gene, a multidrug resistance (MDR) locus that is prevalent in clinical isolates of this important human pathogen. In this paper we demonstrate that the range of structurally diverse compounds capable of inducing qacA transcription is significantly more varied than previously appreciated, particularly in relation to bivalent cations. For all of the newly identified inducing compounds, induction of qacA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 39 publications
(86 reference statements)
3
72
0
Order By: Relevance
“…The affinities of AcrR to its drugs are in the micromolar region, and the dissociation constants are quite similar to those of QacR [25], BmrR [26], and TtgV [27]. Based on the fluorescence polarization assays, titrations of AcrR to the ligand binding solutions give a stoichiometry of 1:1 monomeric AcrR-to-drug molar ratio.…”
Section: Discussionmentioning
confidence: 83%
“…The affinities of AcrR to its drugs are in the micromolar region, and the dissociation constants are quite similar to those of QacR [25], BmrR [26], and TtgV [27]. Based on the fluorescence polarization assays, titrations of AcrR to the ligand binding solutions give a stoichiometry of 1:1 monomeric AcrR-to-drug molar ratio.…”
Section: Discussionmentioning
confidence: 83%
“…It has been suggested that binding of the first QacR dimer forces this energetically unfavorable conformational change, which in turn produces an optimal DNA conformation for the easy binding of the second dimer (351). Experimental data reported by Grkovic et al (121,122) suggested that the two dimers must bind simultaneously and cooperatively to the operator in order to maintain the DNA deformation detected in the crystal.…”
Section: Qacr Regulatormentioning
confidence: 99%
“…QacR is released from the qacA operator by its interaction with a number of cationic lipophilic drugs such as rhodamine 6G, crystal violet, and ethidium (119). More recently, Grkovic et al (122) showed that effector recognition of QacR can be extended to several bivalent cationic dyes and plant alkaloids. In spite of the existence of two binding pockets, only one drug molecule is bound by each homodimer, as determined by equilibrium dialysis studies and isothermal titration calorimetry for the QacR-R6G complex (350).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Like LfrR, the majority of QacR-ligand structures show a single ligand within one monomer of each dimer. However, one structure of QacR in complex with two different ligands, ethidium and proflavine, within the same monomer has been solved (60). For CgmR, different binding stoichiometries are seen for different drugs, and the size of the drug is thought to play a role in the number of molecules required for CgmR derepression (43).…”
Section: Tfr-ligand Interactionsmentioning
confidence: 99%